Der negative Selbstbezug des Absoluten: Untersuchungen zu Nicolaus Cusanus' Konzept des Nicht-Anderen - Rohstock, Max (Quellen und Studien zur Philosophie, 2014)
Nicolas of Cusa's notion of God as "not-other" is one of the most spectacular ideas in the history of metaphysics- the negative self-reference of the Absolute. In this study, Max Rohstock examines this concept historically and systematically. For the first time, he shows Johannes Scotus Eriugena was the true progenitor of the concept